Educational program promoting regular physical exercise improves functional capacity and daily living physical activity in subjects with knee osteoarthritis - Rodrigues Da Silva, José Messias [UNESP]; De Rezende, Márcia Uchoa; Spada, Tânia Carvalho; Da Silva Francisco, Lucila; Sabine De Farias, Fabiane Elize; Clemente Da Silva, Cleidnéia Aparecida; Cernigoy, Claudia Helena De Azevedo; Greve, Júlia Maria D'Andréa; Ciolac, Emmanuel Gomes [UNESP] (Springer Nature, 2017)
Background: Physical exercise and educational programs promote several benefits for patients with knee osteoarthritis (OA). However, little is known about the effects of educational programs promoting the regular practice of physical exercise. The purpose of the present study was to assess the effect of an interdisciplinary educational program, emphasizing the recommendation for regular practice of physical exercise, on functional capacity and daily living physical activity in individuals with knee OA. Methods: Two hundred and thirty-nine individuals (50 men) with an established diagnosis of knee OA (degree I to IV in the Kelgreen and Lawrence scale) were randomly allocated into a multidisciplinary educational program (EDU; n = 112) or control group (CON; n = 127). Functional capacity (sit and reach, 6-min walking test (6MWT), timed up and down stairs test, timed up and go test (TUGT), and five times sit-to-stand test (FTSST)) and daily living physical activity (IPAQ, short version) were measured before, during (6 months) and after 12 months of follow-up. Results: Body mass index reduced significantly (P < 0.05) after 6 months, and remained reduced after 12-month of follow-up in EDU, but not in CON. EDU group improved (P < 0.05) timed up and down stairs (19%), TUGT (32.5%) and FTSST (30%) performance after 6 months of follow-up, which remained improved after 12 months of follow-up. Functional capacity did not change in CON, excepted for the timed up and down stairs performance that increased after 6 months (12%, P < 0.05), but returned to levels similar to baseline after 12 months of follow-up. There was also an increase (P < 0.05) in the prevalence of active and very active individuals, as well as a reduction (P < 0.05) in the prevalence of sedentary individuals in EDU group during follow-up. There were no significant changes on sit and reach and 6MWT performance during follow-up in both groups. Conclusions: The results suggest that an educational program emphasizing the recommendation for regular practice of physical exercise may be an effective tool for improving functional capacity and daily physical activity in individuals with knee OA. Trial registration: NCT 02335034, December 22, 2014.
Keywords: Daily living physical activity; Educational program; Functional capacity; Osteoarthritis; Physical exercise; Physical fitness